Região, regionalização e rede política: um estudo sobre a atuação da Associação dos Municípios do Araguaia-Tocantins (AMAT) - RODRIGUES, Marcos Mascarenhas Barbosa (2006)
The discussion on region intends to let subsidies to understand the territorial dynamics ones in Brazil and his implications at regional level having like his principal agent of a new proposal of regionalization for the Para to Association of the Municipal districts of the Araguaia-Tocantins (AMAT). Whose implication turns in the new forms of conceiving the region and sweats form of practice methodological, the regionalization, being used in this work while instrument for confirmed that hypothesis. Having how problematic: In which measure is it possible to bring into effect a regionalization of the state of the Para, from the arrangements partner-politician with which they are established representative, from the actions of the AMAT? What took the political net constituted by the AMAT in the south-east of the Para to be differentiated and to consolidate in the form to have distinction in the State? Does the establishment of the political nets have the capacity of incorporating the territorial dimension in the execution of his strategies to think and to manage a regional project near the informing local authorities, consequently improving the municipal acting? Having like central hypothesis, that the process of concentration of the political net in the south-east of the Para is responsible it shears insurgence of process of new sub-regionalization like that we see with the proposal of creation of a new state, with the dismemberment of the big-region of the south-east from Para. The methodology way by it through the historical reconstitution of the territorial transformations, with sights to understand the new regionalization, from a vision of totality of which our cutting out makes part and suffers criticism, using interviews, secondary inquiry and bibliographical study.